Kerangka penubuhan institusi pendidikan melalui pembiayaan dana zakat / Azman Ab Rahman … [et al.] - Ab Rahman, Azman; Musa, Zahari Mahad; Yaakub, Nor Asiah; Anwar, Siti Martiah (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2015)
Education is a basic need for all people and to ensure this, it needs continuous financial allocation. Some of them do not receive an education because of poverty and lack financial restraints. The poor and needy only relied on education alms in order to pay the fees and any education aids. The purpose of this research is to recognise education institution that operated fully based on zakat funding. Nevertheless, it also to evaluate schemes and zakat financial aids given to the poor and needy. Therefore, this research will suggest to establish an education institution model based on zakat funding. This research was undertaken using a qualitative method by collecting data based on library research and reports from Baitulmal, Majlis Agama Islam and Pusat Zakat in Malaysia. As a result of these findings, this research points to establish an education institution model through the zakat funding. This is because zakat funding plays a continuous roles and it increases year by year.